INTEGRATION OF STAKEHOLDERS IN THE IMPLEMENTATION OF CDIO IDEOLOGY - Svetlana I. Osipova; Edward A. Rudnitskiy (Высшее образование в России, 2016)
The problem of integration of all interested parties (stakeholders) in the process of implementation of the innovative educational program “Metallurgy” is actualized to eliminate systemic gap between labor market needs and provided educational services. The innovative process of the implementation of the educational program is adequate to CDIO logic (Conceive-Design-Implement-Operate): the adoption of CDIO ideas; the development of innovative educational program; educational program implementation in educational practice; dissemination of the concept and implementation of the components of changes inthe social and educational milieu. The stages of team formation of stakeholders are distinguished, the criteria for selecting team member are proposed.